Assessment of Feedback Environment for Medical Assistant Students in Clinical Areas: Localization, and Validity and Reliability Assessment of the Tool - Marjan Jalali; Arash Najimi; Athar Omid (مجله دانشکده پزشکی اصفهان, 2020)
Background: Clinical education and providing feedback are the most important criteria of vocational education in order to consolidate students' learning. Since evaluation of clinical teaching environment with using a suitable tool plays an important role in enhancing students' motivation and learning, so this study aimed to provide a localized tool for examining feedback environment in clinical field in medical assistant students of Isfahan University of Medical Sciences, Iran.